Pengembangan Kompetensi Pedagogi Mahasiswa Calon guru Biologi melalui Magang Kependidikan Berbasis Lesson Study: Pengabdian - Muhammad Rhesa; Nur Aisyah Ainun; Arifah Novia Arifin; Yusuf Arisandi; Faisal (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service activity was motivated by the need to improve the pedagogical competence of prospective biology teachers so that they are professionally prepared to meet the demands of teaching in schools. The main objective of this activity was to develop the pedagogical competence of prospective biology teachers through education internships based on lesson study integrated with teaching practice at partner schools. The activity was carried out using a participatory approach involving students, supervising lecturers, and Biology teachers from partner schools. The activity was carried out through stages of collaborative lesson planning, classroom teaching, systematic lesson observation, and joint lesson reflection. The subjects of the activity were 20 prospective Biology Education teachers who were divided into several small groups, with each group carrying out at least one complete lesson study cycle. The results of the activities showed a quantitative increase in students' pedagogical competence, with the average questionnaire score increasing from 2.60 at the beginning to 4.21 at the end. Each group of students showed an improvement in their ability to develop Biology learning tools with a rating of very good, as well as an improvement in their observation and reflection skills with a rating of good to very good. Biology teachers from partner schools were actively involved in all stages of learning reflection and provided pedagogical feedback that contributed to improving the quality of learning. The benefits of the activity were felt by students through an improvement in their reflective pedagogical skills, and by partner schools through the strengthening of a culture of collaborative learning reflection. The conclusion of the activity shows that lesson study-based educational internships make a new and important contribution to increasing the involvement of students and teachers in the development of reflective and sustainable Biology learning.